Preventive effects of hydroalcoholic extract of saffron on hematological parameters of experimental asthmatic rats - Somayyeh Vosooghi; Maryam Mahmoudabady; Ali Neamati; Heydar Aghababa (Mashhad University of Medical Sciences, 2013)
Objective: Asthma is a chronic inflammatory disease of the respiratory airways distinguished by edema and infiltration of inflammatory immune cells. To test our hypothesis about the anti-inflammatory effect of saffron, we examined effects of Crocus sativus (C. sativus) extract as a prophylactic anti-inflammatory agent in sensitized rats. Materials and Methods: To induce experimental asthma, rats were sensitized with injection and inhalation of ovalbumin (OA). Forty male Wistar rats were divided into 5 groups (n=8 for each): control, sensitized (asthma), and sensitized and pretreated with three different concentrations of extract, 50, 100, and 200 mg/kg, 2 times a week (group asthma+50EX, group asthma+100EX, and group asthma+200EX). After 32 days, total white blood cells (WBC) counts, red blood cells (RBC), and platelet counts in blood were examined. Results: Total WBC number and eosinophil and neutrophil percentage in blood were increased, but lymphocyte decreased in sensitized animals compared with those of control group (pConclusion: Our findings indicated that the extract of C. sativus could be useful to prevent asthma as an anti-inflammatory treatment.